Ergonomic Evaluation of Push-Pull Type Weeders with Women Operators - Behera, B K; Swain, S; Mohanty, S K (Journal of Agricultural Engineering, 2007)
Evaluation of three weeders namely, rotary peg weeder (RPW), wheel hoe (WH) and wheel finger weeder (WFW) showed that WFW had highest effective field capacity (0.0315 ha/h) and weeding index (77.2%) followed by WH (0.0295 ha/h and 71%) and RPW (0.0195 ha/h and 70.80%). The pushing force to operate the weeder was 142±3.09, 164±4.22 and 126±2.37 N in case of RPW, WH and WFW respectively. The working heart rate varied between 115.80±1.47 to 128.70±1.67 beats/min with the highest value in case of WH and the lowest in case of RPW and the work pulse (HRwork - HRrest) was found to be above the allowable limit of 40 beats/min for WH (50±0.89) slightly below than that for RPW (39±1.58 beats/min) and WFW (38±1.85 beats/min). Work Load (WL), which is oxygen consumption rate (OCR) as percentage of V02 max, was found to be 34±3.2, 52±2.3 and 37±1.74 % for RPW, WH and WFW respectively. The Acceptable Work Load (AWL) for Indian workers is 35 % of the V02 max, The energy expenditure rate (EER) was found to be maximum in WH (19.53 kJ/min) whereas it was 13.67 kJ/min and 12.8 kJ/min in case of WFW and RPW, respectively. The body parts discomfort score revealed that WFW was more comfortable to operate followed by RPW and WH. The grading of work showed that weeding with WH was heavy work whereas it was moderately heavy with RPW and WFW for women operators.